Diarrhoea and constipation in geriatric practice - Ratnaike, Ranjit N. (Cambridge University Press, 1999)
This textbook provides a practical and comprehensive account of the management of diarrhoea and constipation in the elderly. These common disorders in the elderly are not only a burden in themselves but are often manifestations of a more serious underlying illness: thus effective diagnosis and treatment are essential to improve quality of life. Many important conditions are associated with diarrhoea. The text includes updates on pathogenesis, diagnosis and treatment, and highlights the vulnerability of the elderly in regard to acquiring diarrhoea and its complications. The aetiology of diarrhoea is explained, including infections of the gastrointestinal tract, and systemic diseases of which diarrhoea is a manifestation. Diverse disciplines are spanned: from immunology and physiology to microbiology, nutrition and psychiatry. The aetiology, diagnosis and treatment of constipation are dealt with, emphasising practical management issues. The book is aimed at geriatricians, general practitioners and allied health workers.